International Marketing Ethics from an Islamic Perspective: A Value-Maximization Approach - Saeed, Mohammad (Journal of business ethics, 2001)
International marketing practices, embedded in a strong ethical doctrine, can play a vital role in raising the standards of business conduct worldwide, while in no way compromising the quality of services or products offered to customers, or surrendering the profit margins of businesses. Adherence to such ethical practices can help to elevate the standards of behavior and thus of living, of traders and consumers alike. Against this background, this paper endeavors to identify the salient features of the Islamic framework of International Marketing Ethics. In particular, it highlights the capabilities and strengths of this framework in creating and sustaining a strong ethical international marketing culture. At the heart of Islamic marketing is the principle of value-maximization based on equity and justice (constituting just dealing and fair play) for the wider welfare of the society. Selected key international marketing issues are examined from an Islamic perspective which, it is argued, if adhered to, can help to create a value-loaded global ethical marketing framework for MNCs in general, and establish harmony and meaningful cooperation between international marketers and Muslim target markets in particular.